2013
DOI: 10.1111/sji.12054
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Interleukin‐(IL)‐12p40 are Markedly Increased in Brucellosis Among Patients with Specific IL‐12B Genotypes

Abstract: Brucellosis remains a major zoonosis worldwide. Brucella antigens induce the production of T-helper 1 (Th1) cytokines such as interleukin-12 (IL-12) in humans. We aimed to investigate the association of two single nucleotide polymorphisms (SNPs) in the gene encoding the IL-12p40 cytokine (IL-12B) with brucellosis and to examine the functionality of these SNPs through measuring serum levels of IL-12p40. We genotyped IL-12B gene rs3212227, A>C; rs6887695 G>C polymorphisms in a case-control study on a total of 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 52 publications
1
15
0
2
Order By: Relevance
“…Studies on IL-4, IL-6, and MIF are limited. In one study of the IL-6 promoter polymorphism at position -174 in Spanish brucellosis, the same results were obtained, i.e., there were no differences in the frequencies of IL-6 variants between the patients and controls (24). In contrast, 1 study in our country found that IL-6-174CG genotype was more frequent in patients than in controls (27): the authors claimed that the IL-6-174CG genotype may be a risk factor for the development of brucellosis.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Studies on IL-4, IL-6, and MIF are limited. In one study of the IL-6 promoter polymorphism at position -174 in Spanish brucellosis, the same results were obtained, i.e., there were no differences in the frequencies of IL-6 variants between the patients and controls (24). In contrast, 1 study in our country found that IL-6-174CG genotype was more frequent in patients than in controls (27): the authors claimed that the IL-6-174CG genotype may be a risk factor for the development of brucellosis.…”
Section: Discussionsupporting
confidence: 62%
“…One study suggested that IL-10 modulates macrophage function and contributes to an initial balance between pro-inflammatory and anti-inflammatory cytokines, thereby promoting bacterial survival and persistent infection (23). While other study showed a higher frequency of the -251 IL-8 AA genotype in patients than in controls (19), and the other study revealed a higher frequency of the IL-12B rs3212227 AA genotype in patients than in controls (24). Furthermore, the latter study suggested that the rs3212227 AA variant could contribute to an inherited predisposition to brucellosis.…”
Section: Discussionmentioning
confidence: 59%
“…Recently, it has been demonstrated that the CD28:B7 pathway is important in IFN‐g and TNF‐α production by peripheral blood mononuclear cells from brucellosis patients . The role of this pathway in the immune response is essential, because a signal through CD28 stimulates IL‐2 production and IL‐2R upregulation, leading to T cell proliferation and activation, a process essential to control Brucella multiplication . CTLA4, a member of the immunoglobulin superfamily, is a key component in the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have shown that B. abortus and B. melitensis share the same lineage and differ from B. suis which has undergone few genetic mutations and has diverged from the most recent ancestor of all Brucellae [49]. Increased serum levels of IL-6, IL-8 and IL-12 have been reported in patients with brucellosis, while IL-8-251AA and rs3212227AA genotypes have been found to increase the genetic susceptibility to acquire Brucella infections [50,51]. Additionally, the neutrophil/lymphocyte ratio in the blood has been found to be significantly associated with Brucella infection in humans [52].…”
Section: Pathogenesis Of Brucellosismentioning
confidence: 99%